2021
DOI: 10.1111/1468-0009.12506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID‐19 Emergency and National Lockdown on Italian Citizens’ Economic Concerns, Government Trust, and Health Engagement: Evidence From a Two‐Wave Panel Study

Abstract: Preventive measures such as the national lockdown in Italy have been effective in slowing the spread of COVID‐19. However, they also had psychological and economic impacts on people’s lives, which should not be neglected as they may reduce citizens’ trust and compliance with future health mandates. Engaging citizens in their own health management and in the collaboration with health care professionals and authorities via the adoption of a collaborative approach to health policy development is fundamental to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
1
16
0
3
Order By: Relevance
“…Some research has found that trust held stable during the pandemic. For example, Graffigna et al (2021) conducted questionnaire measurements between March 10 and May 4, 2020, in Italy, and their results showed that people's trust toward authorities remained substantially unchanged. In contrast, there is also evidence showing that trust has consistently changed ( Algan et al, 2021 ; Esaiasson et al, 2021 ; Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some research has found that trust held stable during the pandemic. For example, Graffigna et al (2021) conducted questionnaire measurements between March 10 and May 4, 2020, in Italy, and their results showed that people's trust toward authorities remained substantially unchanged. In contrast, there is also evidence showing that trust has consistently changed ( Algan et al, 2021 ; Esaiasson et al, 2021 ; Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a broader project (“Italian Citizens’ Food Habits Monitoring from a Consumer Psychology Perspective) aimed at monitoring Italian citizens’ habits. Previous publications from this study [ 39 , 40 ] included an early developed scale for the measurement of public health engagement ( Public Health Engagement Scale for Emergency Settings (PHEs-E)) and its first validation.…”
Section: Methodsmentioning
confidence: 99%
“…"Covid-19 testing questions: For the presence of Covid-19 infection, four questions measured on dichotomous scales were used to explore whether the subjects themselves had undergone the polymerase chain reaction (PCR) test for Covid-19 (yes/no) and what was the result (positive/negative), for themselves and their family. These items were also previously used in other researches [22,23].…”
Section: Study Measuresmentioning
confidence: 99%